Nilai-nilai Pendidikan Akidah dalam Doa Nabi Ibrahim (Telaah Tafsir Ar-Rāzī dan At-Ṭabarī padaSurat Ibrahim Ayat 35-41) - Muhammad, Muhammad, Dr. Abdullah Aly M.Ag, Dr, Muthoifin, M.Ag (2016)
The background of this study is lack of human attention to the science of monotheism and many irregularities phenomenon caused by technological advances. Modern humans think that the universe was God and lean everything to the absolute laws of nature. The prayer of Prophet Ibrahim in Qoran sura Ibrahim verse 35-41 contains many of faith educational values, so that researcher interested in studying any faith educational values in the prayer. The purpose of this study are: 1) Knowing how was the interpretation of ar-Razi and at-Tabari against sura Ibrahim verses 35-41 in Tafseer ar-Razi and Tafseer at-Tabari, 2) Mention islamic faith educational values in the prayer of Prophet Ibrahim based from study of Tafsir al-Razi and Tafsir at-Tabari against sura Ibrahim verses 35-41, 3) Mention the implications of faith educational values in Islamic education in Indonesia. This study is a text and documentation study with qualitative research paradigm. The primary data source of this study is Tafseer Razi and Tafseer at-Tabari, and secondary data sources such as books, articles and scientific papers which contain a substance related to the research theme. The analytical method used in this study is content analysis, and study methods of interpretation is comparison method (Muqarin). The results showed that, 1) Ar-Razi in his book brings a lot of related issues to the paragraph, so that readers get a lot avail such extensive knowledge, while At-Tabari in his book brings a lot of history, especially the history that contains the meaning of the word and the meaning of the verse. 2) The faith educational values in the prayer of Prophet Abraham in sura Ibrahim verses 35-41 is believed only God is worthy of worship, believing the names and attributes of Allah, believes the end of the day, and depending on God in all things. 3) The implications of the implementation of faith educational values in the prayer of Prophet Abraham in sura Ibrahim verses 35-41 is easy to enforce Sharia Law, the practice of the consequences of the names and attributes of Allah, improving the quality of faith, strengthen confidence and confirms establishment.